An Overview of a Pediatric Rehabilitation Clinic After the Kahramanmaraş Earthquakes - Zeynep Kıraç Ünal; Keziban Koçyiğit; Emre Adıgüzel; Ece Ünlü Akyüz (Galenos Yayinevi, 2023)
Aim: This study aimed to reveal the characteristics of patients who were rehabilitated in a pediatric rehabilitation clinic after an earthquake disaster. Materials and Methods: The records of earthquake victims who were affected by the earthquakes in Kahramanmaraş on February 6th, 2023 and hospitalized in our Pediatric Rehabilitation Clinic between February 6th and June 6th, 2023 were retrospectively reviewed. The patients' demographic data such as age, gender, the city they lived in, duration of stay under the rubble, presence of crush syndrome and dialysis needs, fasciotomy and hyperbaric oxygen therapy (HBOT) history, amputation status and levels, accompanying fracture, peripheral nerve damage, brain injury and the presence of spinal cord injury were noted. Results: Of the 60 inpatients rehabilitated in our clinic, 31 (51.7%) were female and 29 (48.3%) were male. The mean age of the patients was 10 (±0.76) years. Twenty-two (36.7%) of the patients experienced the earthquakes in Hatay, 21 (35%) in Adıyaman, 13 (21.6%) in Kahramanmaraş and 4 (6.7%) in Gaziantep. The length of stay under the rubble of 50 patients was recorded, with a median of 12 (1-96) hours. Crush syndrome developed in 25 (41.6%) of the patients, and 14 (23.3%) of them needed dialysis. HBOT was applied to 10 (16.6%) children. Peripheral nerve damage was detected in 42 (70%) children by electro-neurophysiological or physical examination methods. The most commonly damaged nerve was the sciatic (16%). Thirty four (56.6%) patients underwent fasciotomy. There were fractures in a total of 13 (21.6%) children. Seven (11.6%) patients had amputations in various parts of the extremities. Five (8.3%) of the patients had varying degrees of traumatic brain injury. Spinal cord damage was not detected in any of our patients. Conclusion: In the pediatric population, musculoskeletal injuries caused by earthquakes and their complications are very important in the development and realization of disaster rehabilitation strategies.